E-Service quality dan price terhadap customer loyalty pengguna Gofood: Peran mediasi customer satisfaction pada Mahasiswa FEB Universitas Dian Nuswantoro - Wismiyanti, Rizki Kamila; Perdana, Tito Aditya; Aqmala, Diana; Anomsari, Ariati (Nur Science Institute, 2025)
This study aims to analyze the influence of e-service quality and price on customer loyalty and to examine whether customer satisfaction mediates the relationship between e-service quality, price, and customer loyalty. The sampling technique used in this study is non-probability sampling, specifically purposive sampling, with respondents consisting of GoFood customers who are students at the Faculty of Economics and Business, Dian Nuswantoro University. The sample size consisted of 100 respondents, and data were collected using a structured questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM)-PLS to test both direct and indirect effects between variables. The results indicate that both e-service quality and price have a positive influence on customer satisfaction. E-service quality also has a significant positive influence on customer loyalty, while price does not have a direct effect. Furthermore, customer satisfaction has a significant influence on customer loyalty and serves as a mediating variable in the relationship between e-service quality, price, and customer loyalty. These findings underscore the crucial role of service quality and customer satisfaction in fostering loyalty among digital food delivery customers.